(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Consumer preferences, satisfaction, and store choice factors of organized retail in Bhopal were the subjects of this study. Using a descriptive research design, primary survey data was collected and analyzed at various levels to compare the prominent discount retailer, D-Mart, with alternative retailers. The results indicate that D-Mart's strong preference in the market is due to both aggressive pricing and product mix but does not correlate with a commitment to brand loyalty (high overall recommendation scores). There were operational bottlenecks that created friction between customers (crowd control/billing). Therefore, the cost-experience trade-off suggests that even though value-based pricing would attract customers and ultimately drive sales, for continued customer loyalty businesses will need to find a combination of affordability with the operational excellence of providing great experiences. This study suggests that the increasing importance of experience-driven variables affects how customers view and recommend products and services to others. This research extends knowledge on organized retail by examining Tier-2 urban markets rather than larger metropolitan markets. Retailers should be aware of the implications for their ability to provide both a low-cost and exceptional service or customer-centric operation.